PENGARUH KUALITAS PRODUK, CITA RASA, DAN PROMOSI TERHADAP TINGKAT PENJUALAN PADA OUTLAT MINUMAN ICE SIBOT SELAMA PANDEMI COVID-19 DI KOTA SALATIGA - Anita Dwi Sundari; Nunuk Supraptini; Sri Rahayu (BISECER (Business Economic Entrepreneurship), 2022)
The difficulty of obtaining raw materials from suppliers as a result of the covid-19 pandemic has resulted in the quality of the Ice Sibot Drink product decreasing, this has resulted in complaints from consumers. The absence of product differentiation, the taste of Ice Sibot Drinks is still less attractive to consumers. The promotions that have been carried out have not been consistent and on a large scale so that the information conveyed to consumers is not large enough. These factors were identified as the cause of the decline in sales of Ice Sibot Drinks.In this study the method used is quantitative research with the independent variables used are product quality, taste, and promotion and the dependent variable is the level of sales. The sample in this research is 100 respondents. Questionnaire data collection techniques, data analysis techniques using SPSS version 23 data processing program.Furthermore, the study found that product quality, taste, and promotion of the level of sales of Ice Sibot Drinks in Salatiga City during the covid-19 pandemic. With the value of the correlation coefficient of product quality of 0.727, taste of 0.748 and promotion of 0.753. In addition, product quality, taste, and promotion also have an influence on the level of sales as indicated by the regression coefficient value for product quality of 0.785, taste of 0.687 and promotion of 0.682. Effect of product quality, taste, and promotion together – the same effect on the level of sales is shown from the results of the determination test of 0.64.5% with a value of Fcount (60.954) > Ftable (3.09) with a significance of 0.000 which is smaller than a significance level of 0.05.